HUBUNGAN ANTARA KEJADIAN MULTI-DRUG RESISTANT TUBERCULOSIS (TB-MDR) TERHADAP PENDERITA DIABETES MELITUS - Sirait, Debora; Pakpahan, Edwin; Tarigan, Juliyanti (Jurnal Kedokteran Methodist, 2019)
Background : Diabetes mellitus is a serious health problem that can increase the risk of active tuberculosis two to three times, which is poor blood sugar control and exposure to droplets so that it develops into Mycobacterium tuberculosis infection, which is the main cause. Mycobacterium tuberculosis can cause decreased cellular immunity and increased insulin resistance and decreased insulin production, which can lead to treatment failure and cases of relapse which can lead to the occurrence of Multi-drug resistant tuberculosis (MDR-TB). Methods : The research used literature review method using secondary data. Data were collected using documentation techniques. The research journals used are 7 journals, both national and international journals with a publication deadline for the last 5 years and use Indonesian and English. The inclusion criteria used in this study were multi-drug resistant tuberculosis (MDR-TB) patients with comorbid diabetes mellitus. Conclusion : There is an association between HbA1c levels, body mass index (BMI) and the patient's previous treatment history of the incidence of Multi-drug resistant tuberculosis (MDR-TB) and comorbid diabetes mellitus.